An experimental study of solid and liquid aerosol transport in a horizontal square channel. Issue 12 (1st December 2020) - Chavez, R.; Orea, D.; Choi, B.; Nguyen, T. D.; Anand, N. K.; Hassan, Y.; Sabharwall, P.
Abstract: Various industrial applications such as medical/pharmaceutical sprays, heating, ventilation and air conditioning systems, and other solid/liquid atomization processes benefit from the characterization of flow and deposition mechanisms of solid/liquid aerosols. This work aimed to experimentally study the transport of solid and liquid aerosol particles which represented aerosolized fission products in a nuclear reactor. We measured the flow field, free-stream concentration, and surface deposition of solid/liquid aerosols flowing in a horizontal square channel with Reynolds number of 750–7, 000. Particle image velocimetry (PIV) was applied to acquire the flow field characteristics such as mean velocity fields and turbulent kinetic energy. The effects of Reynolds number and particle diameter were investigated by studying the particle deposition and penetration of two micron-sized particle types. The experimental results of particle deposition velocity agreed well with the correlations published previously and with the associated numerical results. For the Reynolds numbers tested in this study, solid and liquid particle deposition was found to be governed by gravitational sedimentation. Increasing the Reynolds number for a given particle diameter increased the particle relaxation time and penetration efficiency but decreased the particle deposition velocity. Decreasing the particle diameter for a given Reynolds number increased the effect of gravitation sedimentation. By altering the surface properties with the addition of a carbon nanotube coating, the penetration was shown to decrease for the same flow conditions when compared with a smooth surface. Secondary flow vortices located in the corners, unique to turbulent flow in a square channel, were experimentally shown to increase particle deposition in the corners. Copyright © 2020 American Association for Aerosol Research